(untitled) (CIPEEX, 2025)
Introduction: The subjective perception of stress has increased among workers in the industrial sector. Stress is known to impair cardiovascular health and is associated with several cardiovascular diseases. Objective: To evaluate the subjective perception of stress and CVS among workers in the industrial sector and compare them according to gender. Methods: This is a cross-sectional analytical study conducted with industrial workers. The sample included 82 participants, 32 women (39%) and 50 men (61%). Occupational stress was assessed using the Job Stress Scale (JSS), while cardiovascular health was assessed using the American Heart Association (AHA) metrics, through Life Essential 8. Results: There was no association between gender and stress perception (p=0.406). Women use more medication than men (34.4%, p=0.030), but had better systolic blood pressure (SBP) values (∆= -7 mmHg, p=0.014) and better diet quality ((∆= +5 points, p=0.002). There was an association between gender and diet (p=0.003). Most men (22.0%) had low VMS for diet, while women had high VMS for diet (31.3%). Conclusion: Women had better results for SBP and diet score, and it is worth highlighting the importance of assessing VMS in industrial workers, which can help establish strategies to encourage proper nutrition and blood pressure control.